Beware of the Dark Side: The Rise of Cybercrimes - Daxeshkumar Joshi (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
This study paper offers a top to bottom assessment of the mind boggling hardships introduced by cybercrime in India, pushed by the country’s quick digitalization in different areas. The expansion in cybercrime occurrences, enveloping monetary extortion, information breaks, and cyberattacks, has arisen as a critical concern for partners in both public and business areas. This report investigations the essential drives executed by the Indian government, policing, and business elements to counter these difficulties. It inspects the developing complexities of digital dangers, evaluates the viability of current relief methods, and proposes thoughts for making a more adaptable and powerful network protection structure. The report offers fundamental bits of knowledge to upgrade India’s safeguard against the raising scene of computerized dangers by tending to the essential causes and advancing nature of cybercrime in the country. The discoveries look to further develop India’s online protection foundation and reinforce strength against expanding digital dangers.